The Psychology and Parapsychology of Spiritual Emergency - Storm, Lance; Goretzki, Monika (Journal of Scientific Exploration, 2021)
A defining aspect of Spiritual Emergency (SE) is ‘psychic opening’ which may predict psi performance. This study tested paranormal (psi) performance of individuals who have or have had experiences of spiritual emergency (i.e., ‘SE-Experients’), and compared their performance against controls. The study also assessed psychological aspects of SE to differentiate it from psychosis and other proposed psi-inhibitive symptoms—namely, alogia (i.e., poverty of speech), depression, anxiety, and stress. Two groups of participants were formed: controls (mainly Psychology students) and SE-Experients. Participants either completed the study on computer in the laboratory or online. Questionnaires on spiritual emergency (which includes a subscale on psychic opening), positive symptoms of psychosis, alogia, spiritual identity, paranormal belief, mysticism, depression, anxiety, and stress, were administered to participants, who then completed the Imagery Cultivation (IC) picture-identification psi task, which uses a shamanic-like journeying protocol (Storm & Rock, 2009). The differences between controls and SE-experients on the psi measures, direct hitting (as a percent hit-rate) and mean rank scores, were not significant, but the sum-of-ranks difference was highly significant. Also, SE-experients had a marginally significant mean rank score. Direct hitting did not correlate significantly with any variable, except rank scores, which correlated significantly with psychic opening, spiritual identity, and paranormal belief, and marginally significantly with spiritual emergency. Direct hitting, rank scores, and SE did not correlate significantly with alogia, depression, anxiety, or stress, but the psychosis measure did correlate significantly with alogia, depression, anxiety, stress, and SE. The statistical evidence suggests some proportion of SE-experients experience psychic opening. While SE and psychosis overlap, only SE was predicted by spiritual identity, extrovertive mysticism, and paranormal belief (but not alogia), whereas psychosis was predicted by alogia only.